Cloud computing and its key techniques - Xu Wang; Beizhan Wang; Jing Huang (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
With the development of parallel computing, distributed computing, grid computing, a new computing model appeared, called cloud computing. It aims to share data, calculations, and services transparently among users of a massive grid. It became a hot issue for its advantages such as "reduce costs", "increase business flexibility" and/or "provide business continuity". In this paper, we described what is cloud computing and took Google's cloud computing techniques as an example, summed up key techniques, such as data storage technology (Google File System), data management technology (BigTable), as well as programming model and task scheduling model (Map-Reduce), used in cloud computing, and then some example of cloud computing vendors were illustrated and compared.